Delving Tertiary EFL Students’ Perceptions on Peer Assessment to Improve Critical Thinking in Writing - Asirah, Asirah; Saputra, Nizar (IJELR: International Journal of Education, Language, and Religion, 2024)
The primary objective of this study is to explore how English Department students perceive peer assessment as a means to enhance critical thinking in writing. The research involved forty English students who had previous experience with peer assessment in their writing class. Data collection was achieved through a four-point Likert-Scale questionnaire and semi-structured interviews. Qualitative data analysis using thematic analysis was employed to analyze the collected data. The findings indicated that the majority of students (92.84%) viewed peer assessment positively, as they believed it raised their awareness and consciousness of writing skills. Moreover, 81.89% of students expressed that peer assessment was beneficial in fostering better critical thinking skills, leading them to approach writing more critically. Students generally regarded their peers as capable of providing valuable feedback on their writing, resulting in improved critical thinking due to the reviews they received or provided. However, a small number of students had negative perceptions of peer assessment for improving critical thinking. Their reluctance stemmed from low motivation to actively participate in the peer assessment process and the belief that their friends evaluated their writing unfairly based on personal relationships.